2017
DOI: 10.1038/srep43009
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure in the remote period after the Chernobyl accident caused oxidative stress and genetic effects in Scots pine populations

Abstract: Even 30 years after the Chernobyl accident, biological effects of irradiation are observed in the chronically exposed Scots pine populations. Chronic radiation exposure at dose rates above 50 mGy∙yr−1 caused oxidative stress and led to the increase of antioxidants concentrations in these populations. Genetic variability was examined for 6 enzymes and 14 enzymatic loci of 6 Scots pine populations. Dose rates over 10 mGy∙yr−1 caused the increased frequency of mutations and changes in genetic structure of Scots p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 34 publications
(42 reference statements)
2
17
0
1
Order By: Relevance
“…Studies on the accumulation of radionuclides in small mammals within this area in the late 1990s suggested that chronic dose rates could be as high as 86 mGy/day for the duration of their lifecycle (Chesser et al, , ). Similarly, many of the studies demonstrating genetic effects in scots pine are based on trees receiving doses orders of magnitude higher than the present study (Kuchma, Vornam, & Finkeldey, ; Vornam, Arkhipov, & Finkeldey, ), though effects at lower doses have also been recorded (Geras'kin & Volkova, ; Volkova, Geras'kin, & Kazakova, ).…”
Section: Discussionsupporting
confidence: 58%
“…Studies on the accumulation of radionuclides in small mammals within this area in the late 1990s suggested that chronic dose rates could be as high as 86 mGy/day for the duration of their lifecycle (Chesser et al, , ). Similarly, many of the studies demonstrating genetic effects in scots pine are based on trees receiving doses orders of magnitude higher than the present study (Kuchma, Vornam, & Finkeldey, ; Vornam, Arkhipov, & Finkeldey, ), though effects at lower doses have also been recorded (Geras'kin & Volkova, ; Volkova, Geras'kin, & Kazakova, ).…”
Section: Discussionsupporting
confidence: 58%
“…This ‘moisture‐effect’ has been attributed to indirect IR‐induced damage of cellular constituents via reactive oxygen species (ROS) or reactive nitrogen species (RNS) which are ubiquitously produced by radiolysis of water (Desouky, Ding, & Zhou, 2015; Riley, 1994; Wardmann, 2009). Thus, besides direct cellular damage, IR also induces oxidative stress in cells and it is argued that such free radicals are the major source for IR‐based cellular damages in plants and animals (Caplin & Willey, 2018; Danchenko et al, 2016; Foyer & Noctor, 2016; Garrison, 1987; Volkova, Geras'kin, & Kazakova, 2017). Brewbaker et al explain the observed differences in radiation‐sensitivity between desiccated and hydrated pollen by effects of the oxygen level, because anoxic conditions remove the effect (Brewbaker & Emery, 1962).…”
Section: Factors Influencing Radiation‐susceptibility Of Pollenmentioning
confidence: 99%
“…There have been numerous reports of changes in anti-oxidant concentrations due to chronic exposure to low-dose IR (often with reports of oxidative ‘stress’) ( Einor et al, 2016 ; Volkova et al, 2017 ), and some studies consider that the ‘dominating effect of IR in cells is the formation of free radicals from water or oxygen’ ( Danchenko et al, 2016 ), but we suggest that these claims must be considered within an appropriate stress response context for higher plants. Not just in plants but in any aerobic organism, the disturbance of the delicate redox balance of life, rather than a change in anti-oxidant concentration, underpins oxidative stress.…”
Section: Plant Biology and Ionizing Radiation – A Stress Response Conmentioning
confidence: 93%
“…However, recent studies at this location have supported the assertion that P. sylvestris is particularly sensitive to IR. They have noted an increased frequency of gene mutations at 1.14 μGy/h (10 mGy/a – below the low end of the DCRL for P. sylvestris ) and changes in anti-oxidant concentrations at 5.7 μGy/h (50 mG/a – just in the range of DCRL for P. sylvestris ) ( Volkova et al, 2017 ). It is notable that of the many endpoints measured in these studies, there are some in which significant effects of IR are reported, especially cytogenetic ones, but that these are not, overall, adverse enough at the level of the individual or above to merit a reconsideration of the DCRLs.…”
Section: The Effects Of Ionizing Radiation On Plantsmentioning
confidence: 99%